Wound healing in glaucoma surgery. Part 3. Methods of preoperative prevention - S. Yu. Petrov; E. V. Yani; O. M. Filippova; A. D. Epkhieva (Российский офтальмологический журнал, 2025)
Study of factors preventing excessive scarring in antiglaucoma surgery creates a foundation for developing methods of influencing these processes in the postoperative period in order to increase the effectiveness of the intervention. Analysis of the literature showed that a systematic approach to preparing for successful surgical treatment of glaucoma should include a rational choice of previous hypotensive therapy with preservative-free drugs, prevention of damage to the ocular surface using tear substitute and immunosuppressive therapy, as well as preoperative anti-inflammatory prophylaxis with steroid and non-steroid agents with proven ophthalmic hypertension safety.